Gallbladder torsion in an 11-month-old Labrador Retriever - Theurer, Jannina; Himmelsbach, Peter; Sinzinger, Wolfgang; Hartmann, Antje (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2023)
An intact male Labrador Retriever was presented with signs of an acute abdomen and generalized weakness. Abdominal ultrasonography revealed a distended, horizontally orientated and caudally displaced gallbladder with a thickened wall. Computed tomography (CT) showed an abrupt tapering of the cystic duct in addition to the displacement of the gallbladder.On laparotomy a complete gallbladder torsion was diagnosed. After cholecystectomy the dog made a full recovery. Gallbladder torsion should be considered as a rare, potential differential diagnosis in dogs with an acute abdomen.
Keywords: Ultrasonography; computed tomography; acute abdomen, laparotomy